Self-perceptions and social-emotional classroom engagement following structured physical activity among preschoolers: A feasibility study - Spyridoula Vazou; Constantine Mantis; Gayle Luze; Jacqueline S. Krogh (Elsevier, 2017)
Background: The well-rounded development of the child, including physical, cognitive, emotional, and social health, may be the most efficient route to well-being and academic success. The primary goal was to investigate the feasibility of implementing a 12-week structured program of physical activity (PA) incorporating cognitive, social, and emotional elements in preschool. Additionally, this study, using a within-subject design, examined the acute effects of a PA session on classroom engagement and changes on perceived competence and peer acceptance from the first to the last week of the program. Methods: Twenty-seven preschoolers (mean age = 4.2 years) completed the Pictorial Scale of Perceived Competence and Social Acceptance for Young Children before and after a twice-weekly PA program. Unobtrusive classroom observations were conducted for verbal, social, and affective engagement during the first and last week of the program, both following a structured PA session (experimental day) and on a day without PA (control day). Treatment fidelity was monitored to ensure that the intervention was delivered as designed. Results: The children exhibited longer periods of verbal and social engagement during classroom periods that followed PA sessions than on non-PA days. Children also expressed more positive affect following PA sessions during the last week of the PA program. Despite high baseline scores, perceptions of general competence increased meaningfully (η2 = 0.15, p = 0.05), driven by increase in perceptions of cognitive competence (η2 = 0.15, p = 0.06). Conclusion: This study demonstrates the feasibility of providing structured PA program to preschoolers. Moreover, these initial findings suggest that purposely designed, structured PA may help advance the social-emotional engagement and perceived competence of preschool children.